Detecting Water in Honeycomb Composites by Acoustic Emission during Freezing or Melting - Helge Pfeiffer; Tian Xun Lin; Jeroen Soete; Johan Vanhulst; Dimitrios Chronopoulos (e-Journal of Nondestructive Testing)
Water trapped in sandwich honeycomb composites—due to defects, diffusion, or other factors—is a major concern, especially in aircraft maintenance. In this paper, we present a method based on acoustic emissions for the quick assessment of possible water ingress that can be performed when a structure is exposed to freezing or melting conditions, such as during ascent or descent in high-altitude flights or after landing. A quantitative analysis, including exponential decay models and amplitude and frequency distributions, confirm that melting ice can be detected not only locally but also in its vicinity. The presented method is compared with respect to active ultrasonic transmission tests.